2020
DOI: 10.14202/vetworld.2020.1030-1036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of farnesol and lyticase on the formation of Candida albicans biofilm

Abstract: Background and Aim: Candida albicans is a dimorphic fungus that has both yeast and filamentous forms. It is part of the normal flora in the oral and genital areas of mammals. One factor for the pathogenicity of C. albicans is its ability to switch from yeast to hyphae. The hyphal form adheres and penetrates tissues more readily than the yeast form and produces biofilms that are associated with chronic infection. Biofilms are protective niches that enable microorganisms to be more resistant to antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 20 publications
(26 reference statements)
0
23
0
Order By: Relevance
“…Farnesol inhibited filamentation [ 25 ] including hyphal initiation [ 5 , 13 , 26 ], and filamentous growth while not disrupting their growth rates. In addition, farnesol blocked the yeast-to-hypha transition for a period of at least 6–10 h after germ-tube formation but did not block preexisting hyphal elongation [ 4 , 27 ]. It was reported that farnesol induced apoptosis in C. albicans via the accumulation of reactive oxygen species (ROS), mitochondrial degradation, and caspase activation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farnesol inhibited filamentation [ 25 ] including hyphal initiation [ 5 , 13 , 26 ], and filamentous growth while not disrupting their growth rates. In addition, farnesol blocked the yeast-to-hypha transition for a period of at least 6–10 h after germ-tube formation but did not block preexisting hyphal elongation [ 4 , 27 ]. It was reported that farnesol induced apoptosis in C. albicans via the accumulation of reactive oxygen species (ROS), mitochondrial degradation, and caspase activation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In nature, fungi of the genus Candida are widespread. They live on household items and food, primarily on sugar-rich vegetables and fruits, in dairy products as well as in the internal cavities of mammals including humans [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lyticase is an endoglycosidase with an affinity toward β(1–3)-glucans ( 41 ) found in the matrix and cell wall of fungi but not targeted by the endoglycosidases present in the Ce/De/Di cocktail (cellulase and dispersin B). It has already been shown to reduce C. albicans and P. aeruginosa biofilm biomass in vitro ( 42 44 ) or to successfully treat a catheter colonized by a Acremonium fungus when combined with amphotericin B ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a QS molecule, farnesol participates in regulating various physiological processes in Candida , including filamentation, biofilm formation, drug susceptibility, and apoptosis [ 3 , 4 , 16 , 22 ]. This compound is produced by many organisms, mainly fungi and is also found in many essential oils of plants [ 23 ].…”
Section: Discussionmentioning
confidence: 99%